From Diagnosis to Education: Unifying Nursing, Laboratory, and Health Education for Better Health Systems - Mashael Ahmed Bamunif; Abeer Mohammad Bafaraj; Ohoud Eissa Barnawi; Maryam Hassan Atwani (International Journal of Medical Toxicology and Legal Medicine, 2024)
The integration of nursing, laboratory services, and health education is critical to improving healthcare delivery, patient outcomes, and overall system efficiency. This paper explores how unifying these three sectors can address gaps in care, promote interprofessional collaboration, and streamline workflows within healthcare systems. It reviews existing literature on collaborative models in healthcare and proposes a framework for incorporating nursing, laboratory, and health education into a cohesive and holistic care model. The findings suggest that such integration can lead to better patient outcomes, reduce medical errors, improve communication, and contribute to health equity.